Proposing A Method for Assessment of Brand Imitation Factors (2019)
Brand imitation is an approach for new brands to be successful in the market; on the other hand, it can be destructive for developed brands by incurring heavy financial losses. Many studies have investigated imitation and its effective factors. The present paper studies effective factors of imitation and also ranks them through expert judgments. We use rough numbers properties to rank the factors. In so doing, three groups of experts, based in Iran, were asked to rank the factors that affect brand imitation. The ranking process was implemented by Rough-TOPSIS method. Also, the authors apply Fuzzy-TOPSIS method and findings were compared. This study recognizes important factors that affect brand imitation and rank them according to the significance level. Results emphasize that legislation is the most important factor that can prevent brand imitation and counterfeit. This ranking helps companies to improve specifications in order to obtain security for their brands.